2015
DOI: 10.1186/s12985-015-0389-y
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B surface gene variants isolated from blood donors with overt and occult HBV infection in north eastern Egypt

Abstract: BackgroundMajor hydrophilic region in genomic HBV extending from aa99 to aa169, clustered with a highly conformational epitope, is critical to the antigenicity of hepatitis B surface antigen (HBsAg) and may affect the diagnosis of HBV in HBV screening test. So, this study aimed to characterize variants of S gene product of hepatitis B virus (HBV) isolated from patients with overt or occult HBV infection in north-eastern Egypt.MethodsThe study included sera of two different groups of volunteer blood donors (VBD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…The clinical features and pathophysiology of HBV infection are determined by the balance between the host-immune response and viral replication competence. 20 HBsAg is the target of neutralizing antibodies and is encoded by the preS/S gene, which includes the preS1, preS2, and S genes. Mutation of the preS/S gene has been suggested as a factor that influences the balance between host and virus and is associated with OBI.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical features and pathophysiology of HBV infection are determined by the balance between the host-immune response and viral replication competence. 20 HBsAg is the target of neutralizing antibodies and is encoded by the preS/S gene, which includes the preS1, preS2, and S genes. Mutation of the preS/S gene has been suggested as a factor that influences the balance between host and virus and is associated with OBI.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of OBI is difficult to be established, as most of the time it would only be suspected and worked up in some special settings. It may vary substantially in different studies in view of different methodologies (based on serology vs. virology): cryptogenic cirrhosis or advanced liver fibrosis (prevalence, 4 to 38%), [15][16][17] parenteral blood exposure (45%), 18 chronic hepatitis C infection (52%) and human immunodeficiency virus (HIV)-infected patients (0 to 45%), 19 blood donors (0 to 22.7%), 20,21 and hemodialysis patients (0 to 54%). 22…”
Section: Prevalence Of Occult Hepatitis B Infectionmentioning
confidence: 99%
“…Blood transfusion is a key transmission route of OBI provided that the screening of blood donors is less intensive. 105 The prevalence of OBI among blood donors varies from country to country, with the highest reported on in Egypt (anti-HBc, 22.7%; HBV DNA, 22.7%) 20 and lowest in Iran (0%). 21 A study of 14,937 young blood donors born between 1992 and 1997 in China, that is, in the era of universal HBV vaccination program, found that 10 of 14,937 (0.067%) donors had detectable serum HBV DNA.…”
Section: Blood Products Transfusionmentioning
confidence: 99%
“…For these reasons, in some countries such as the USA, Germany, France, Korea, Japan, Thailand, and Australia anti-HBc has been routinely screened together with HBV DNA detection according to each National Blood Bank policy, while in others countries the diagnostic approach may be different (table 1) [13, 29, 62, 71, 75, 77, 79-82, 86, 90, 94]. Moreover, anti-HBc testing was used only for research purposes (table 1) [91][92][93].…”
Section: Anti-hbc: To Test or Not To Test That Is The Questionmentioning
confidence: 99%